2017
DOI: 10.4172/2332-0877.1000333
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Clostridium difficile Infection among Patients Over 90 Years Old

Abstract: Aim: Ageing population trends indicate that the median life expectancy in Japan is increasing. Clostridium difficile infection (CDI) can be a fatal nosocomial infection among the geriatric population. We examined clinical outcome and risk factors associated with death due to CDI among patients >90 years old.Methods: This retrospective observational study was performed to demonstrate the clinical characteristics of Patients >90 years who developed CDI between April 2010 and March 2015 at Tama-Hokubu Medical Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
1
Order By: Relevance
“…Cardiopulmonary diseases and arrhythmia are known risk factors of mortality in CDI patients. 7,30 However, comorbidity of heart failure did not significantly increase the mortality of GDH+ patients in the present study, as shown by univariate analysis (data not shown).…”
Section: Discussioncontrasting
confidence: 37%
“…Cardiopulmonary diseases and arrhythmia are known risk factors of mortality in CDI patients. 7,30 However, comorbidity of heart failure did not significantly increase the mortality of GDH+ patients in the present study, as shown by univariate analysis (data not shown).…”
Section: Discussioncontrasting
confidence: 37%